The inclusion of women in engineering (Research, Society and Development, 2022)
There are many challenges faced by women in the process of entering the job market, especially in some areas of activity such as engineering, which for many years were seen as professional areas aimed at the male universe, where nowadays women have also acted with excellence. Faced with the growth in the supply of undergraduate courses in the area of Engineering and the current predominance of men in the classroom, in the search to identify the main challenges faced by women in the area of engineering, this qualitative and quantitative research was carried out, through the primary data collection method, through a questionnaire directed to the engineers registered at CREA - SP, with the objective of reflecting on this process of professional inequality between men and women, the research brought evidence of moral and gender harassment in the construction of the professional identity, where the greatest difficulty presented by women is related to obtaining equality of opportunity and salary so that they can have a fair space in relation to competitiveness with men.